2017
DOI: 10.3233/nre-171457
|View full text |Cite
|
Sign up to set email alerts
|

Intensive seated robotic training of the ankle in patients with chronic stroke differentially improves gait

Abstract: Joint-specific robotic training of the paretic ankle provided the most benefit to individuals with moderate or mild gait speed impairments after stroke. Baseline gait speed function (low, moderate, high) was associated with three distinct recovery profiles. This suggests that severity-specific intervention may be critical to improving efficiency of stroke recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…As a representative example, Anklebot used a target-based video game to repeat paretic ankle dorsiflexion and plantarflexion a total of 560 times per hour in a sitting position. This type of temporal symmetry [13], and step length symmetry [13], only for moderate to high functional level ankle training showed positive effects on ankle performance, including velocity [14], smoothness [14], and accuracy [14] as well as gait performance, include increased heel touch [14], individuals [15]. As there is a need to focus on more effective ankle strengthening training rather than simple repetitive exercise for stroke patients, understanding motor control will help to develop an ankle control method.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a representative example, Anklebot used a target-based video game to repeat paretic ankle dorsiflexion and plantarflexion a total of 560 times per hour in a sitting position. This type of temporal symmetry [13], and step length symmetry [13], only for moderate to high functional level ankle training showed positive effects on ankle performance, including velocity [14], smoothness [14], and accuracy [14] as well as gait performance, include increased heel touch [14], individuals [15]. As there is a need to focus on more effective ankle strengthening training rather than simple repetitive exercise for stroke patients, understanding motor control will help to develop an ankle control method.…”
Section: Discussionmentioning
confidence: 99%
“…In stroke patients, muscle weakness has been implicated in deficient physical activity on one side of the body and this deficit is more pronounced distally than proximally [23]. A previous study showed There are few targeted training programs or devices that strengthen or educate effectively the distal part of ankle muscles [13][14][15]. As a representative example, Anklebot used a target-based video game to repeat paretic ankle dorsiflexion and plantarflexion a total of 560 times per hour in a sitting position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spasticity occurs more frequently in the upper rather than the lower limbs, and this regional propensity contributes to less recovery of upper limb independence, often resulting in near permanent impairment of the wrist and hand (Sommerfeld et al, 2012). Some investigators have demonstrated that effective upper limb rehabilitation requires intensive, repetitive, activity dependent learning (Chang et al, 2017;Volpe et al, 2009;Lo et al, 2010). However, despite aggressive therapy, residual spasticity frequently inhibits active wrist and finger extension, prohibiting any attainment of new functional capacity.…”
Section: Introductionmentioning
confidence: 99%
“…The robots can also be implemented with games and virtual reality systems to motivate the patient to actively participate in the training session [8][9][10]. Table 1 shows clinical results from trainings with games and virtual reality systems implemented by lower limb rehabilitation robots, namely, Rutgers Ankle [11], Anklebot [12], VRCTS [10]. Therefore, robots for stroke rehabilitation are promising tools to provide optimal recovery outcomes and enhance the productivity of physiotherapists [13].…”
Section: Introductionmentioning
confidence: 99%